Suboptimal control of cardiovascular risk factors in myocardial infarction survivors - Vasco Rafael Sousa Silva (2020)
Introduction and Objectives: As short-term mortality continues to decrease after myocardial infarction (MI), secondary prevention strategies attain increasing relevance in order to prevent recurrent events. This study aimed at evaluating cardiovascular risk factor (CVRF) control, namely dyslipidemia, hypertension and diabetes mellitus, among a contemporary cohort of MI survivors who completed an exercise-based cardiac rehabilitation (EBCR) program. Methods: Observational, retrospective cohort study including patients admitted to a tertiary center with an AMI between November 2012 and April 2017, who completed a phase II EBCR program after discharge. Achievement of LDL cholesterol, blood pressure and HbA1c guideline recommended targets was assessed. Lipid profile parameters were assessed and compared at three separate moments (hospitalization, beginning and end of the program). Results: A total of 379 patients were included. Mean age was 58.8 ± 10.6 years and 81% were male. Considering the ESC guidelines contemporary to the data collection, 61%, 87% and 71% achieved the recommended LDL cholesterol, blood pressure and HbA1c targets, respectively, at the end of the program. Combining all three risk factors, 42% achieved recommended targets. High-sensitivity C reactive protein decreased between the beginning and the end of the program [0.14 (0.08-0.29) mg/L to 0.12 (0.06-0.26) mg/L; p<0.001]. Conclusion: Despite contemporary management strategies, a substantial number of patients presented suboptimal control of CVRF. Considering dyslipidemia, hypertension and diabetes mellitus combined, less than half of individuals achieved the recommended targets. These findings highlight a pivotal unmet need which could be particularly relevant in improving cardiovascular outcomes by enhancing secondary prevention profiles.